Poverty as a socio-cultural phenomenon - D. A. Popravko (Путеводитель предпринимателя, 2020)
The article considers poverty as a socio-cultural phenomenon through the concept of «poverty culture». Selected concepts of structural poverty, persistent poverty, the underclass or the lower class. The characteristic features and peculiarities of the subculture of poverty are marked. It is determined that the main aspect of poverty culture is inheritance of poverty on the basis of negative norms and values.